Employee commitment and organizational performance in selected fast food outlets in Osun State - Ulabor, Ehimen Abiodun; Bosede, Agelebe Ibiwunmi (Goodwood Publishing, 2019)
Purpose: This study examined the effect of employee commitment on organization performance of selected fast food outlets in Osun State. It determined how employee commitment affects staff turnover and also examined factors that affect employee commitment Research Methodology: Primary data was used for this study; respondents were selected using convenient sampling method from the study area. Questionnaire was used to gather information. One hundred copies of questionnaire were administered to the selected respondents and ninety-six were retrieved and found useful for analysis. The data gathered were analysed using both descriptive and inferential statistics. Results: Findings revealed that employee commitment is significant to organization performance. Profitability, increased in sales, and increased in customers’ patronage were used to measure organizational performance, and it was observed that employee commitment influence profitability; increased in sales, customers’ patronage. It was observed that employee commitment affects staff turnover as revealed by the chi-square statistic (?2 =). Likewise, findings showed that employee commitment could be affected by some factors such as gender, nature of work, length of service, and management style, Although, length of service and management style were not significant at 5% significance level. The study concluded that an employee commitment can influence the organization performance. Keywords: Employee commitment, Organization performance, Staff turnover